Orthopedic Implant Removal in Adults: Its Indications and Risks - Muhammad Shoaib Zardad, Syed Usman Shah, Muhammad Ali Usman, Baber Shahzad Sadiq, Syed Maaz Shah, Muhammad Younas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to analyze the outcomes and risks associated with removing extremity implants from adult orthopaedic patients. Study Design: Retrospective Cohort study Place and Duration: Ayub Teaching Hospital Abbottabad and Abbottabad International Medical institute Abbottabad. April 2022 to March 2023 Methods: Total 97 patients were included in tis study. All the patients were underwent for orthopedic implant removal. The reasons for implant removal, as well as any difficulties that arose during or after the procedure, were documented in every case. We analyzed all of the data using SPSS 24.0. Results: There were 66 (68.04%) males and 31 (31.96%) females with mean age 30.78 years. Infection was the most common indication found in 27 (27.8%) cases, followed by pain in 24 (24.7%) cases. Locking compression plates were the most popular method of implant removal, followed by 3.5 mm dynamic compression plates and interlocking nails. Problems with implant access occurred in eleven (11.3%) cases, screw breakage in eight (8.2%) patients, and implant breakage in three (3.1%) patients as a result of the operation. Twelve patients (16.5% of the total) experienced chronic local infection after surgery, and thirty-one (31.95% of the total) reported limb pain after the procedure. Conclusion: Implant removal was most often due to infection in our series. Most post-operative consequences were discomfort and persistent local infection, while implant access and screw breakage were the most prevalent per-operative issues. Keywords: Infection, Implant Removal, Orthopedic